Pembuatan Nugget Ikan Kembung Dengan Penambahan Jamur Tiram - M Fazil; Dewi Fortuna Ayu; Yelmira Zalfiatri (JURNAL AGROINDUSTRI HALAL, 2022)
The purpose of this study was to obtain the best ratio of oyster mushrooms in addition to the quality of mackerel fish nugget. The research method used a completely randomized design CRD experiment consisting of four treatments and four replications. The treatments consisted of KJ1 (ratio of mackerel fish and oyster mushrooms 70:30), KJ2 (ratio of mackerel fish and oyster mushrooms 60:40), KJ3 (ratio of mackerel fish and oyster mushrooms 50:50), and KJ4 (ratio of mackerel fish and oyster mushrooms 40:60). The data obtained were statistically analyzed using analysis of variance and continued with Duncan's multiple range test (DMRT) at the 5% level. The results showed that the ratio of mackerel fish and oyster mushrooms significantly affected moisture, ash, protein, and crude fiber content, as well as descriptive sensory assessments such as color before and after frying, aroma before and after frying, texture before frying, elasticity, taste and overall hedonic assessment. The best treatment was KJ3 (ratio of mackerel fish and oyster mushrooms 50:50) which of 56.45% moisture 1.11% ash, 15.40% protein, and 2.98% crude fiber content. The overall sensory assessment of the nugget was slightly white color before frying, yellowness after frying, a little oyster mushroom flavoring before and after frying, a little soft texture, chewy, and slightly oyster mushroom taste.